A Study of a Heat Exchanger Sizing of a Gas Turbine Inlet Air Cooling for Power Enhancement - Salim, D.A. (Springer, 2020)
A gas turbine operated at the University Technology PETRONAS Gas Turbine District Cooling Plant produces an average of 3258Â kWh with 30 of estimated gas turbine efficiency. A previous study done by the writer has shown of 20 increase in the efficiency of a gas turbine with the implementation of the turbine inlet air cooling. The sizing of the Heat Exchanger needed to be determined as the existing air inlet is only a 30Â ft2 flange attached directly to the compressor of the gas turbine. This studies conclude that a 320Â ft2 heat exchanger is needed in order to reduce the air inlet fluctuations (a range of 23â34Â Â°C) to 15Â Â°C. By placing the heat exchanger in the gas turbine, a significant Pa pressure loss of approximately 187.55 was experienced. Â© 2020, Springer Nature Singapore Pte Ltd.